(untitled) - Silberman, Melvin L. (San Francisco, Calif., 1998)
A new edition of a bestselling book offering over 200 designs and case examples on 35 subjects, including coaching, communication skills, team building, performance appraisals, customer service, problem solving, time management and leadership. With the guidance in this book you will be able to design and conduct experiential programmes in organisations in both the private and the public sector. There is information on assessing training needs, developing active training objectives, preparing effective lectures and ensuring that training is applicable on-the-job.
Keywords: Employees,Người lao động; Training of,Tập huấn